PROTOCOLS OF TREATMENT OF MENINGITIS IN MEDICAL DEPARTMENT: ARE THERE ANY? - Malik, Saqib; Rehman, Najma; Naz, Farhat; Syed, Zainab; Zainab, Zarnab; Irshad, Romana (Journal of Ayub Medical College Abbottabad, 2020)
Background: Meningitis, whether viral or bacterial is associated with high mortality rate and risk of severe lifelong disability. Early antibiotics administration and favourable outcomes have been demonstrated by previous studies. The purpose of the study was to evaluate whether the patients with suspected meningitis in general medicine department of Ayub Teaching Hospital Abbottabad were being managed according to protocols. Methods: This cross-sectional study was carried out in the Medical Department of Ayub Teaching Hospital Abbottabad from March 2018-March 2019 in which data was retrospectively collected from the hospital records of all patients with suspected meningitis admitted in Medical Ward. SPSS version 20.0 was used for data analysis. Results: Out of 41 patients in the study 19 (51.74%) were male. Viral encephalitis accounted for 23 (56.1%) tuberculous meningitis for 14 (34.1%), and 4 (9.8%) patients had septic meningitis. Lumbar puncture for CSF examination was performed in 38 (92.7%). Out of 41 patients, 19 (46.3%) received a combination of Ceftriaxone, Acyclovir and Dexamethasone, 16 (39.0%) patients received anti tuberculous treatment (ATT), Dexamethasone and Streptomycin combination, 3 (7.35%) patients were given Ceftriaxone (2g) and Dexamethasone and 1 ( 2.45%) patient was given a combination of Ceftriaxone(2gm) along with Vancomycin (1gm) and Dexamethasone; while 2(4.9%) patients were given a combination of Acycolvir and Dexamethasone. Conclusion: This study identified practice gaps in the management of patients with suspected meningitis according to guidelines, as lumbar puncture and CSF-RE were not timely done and proper laboratory records were not maintained. Secondly blood culture facilities were not available in the hospital. Keywords: Tuberculous Meningitis; Viral Encephalitis; Lumbar Puncture